Serum Electrolyte and Blood Lipid Profile in Stroke Patients - Tranggono Yudo Utomo; Meriyanti Wimny Gwijangge; Agus Yudawijaya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is a leading cause of death and disability worldwide, including in Indonesia. While vascular factors are the primary cause, metabolic components such as serum electrolytes and blood lipids also play a significant role in the onset and progression of stroke. Imbalances in sodium, potassium, and chloride, as well as abnormalities in cholesterol and triglyceride levels, can influence both stroke risk and prognosis. Understanding these biochemical profiles in stroke patients is essential for improving clinical outcomes. This study aims to analyze the profile of serum electrolytes and blood lipids in stroke patients treated at Dr. Chasbullah Abdulmajid Hospital, Bekasi City, during the period December 2024 to March 2025. Stroke is one of the leading causes of morbidity and mortality worldwide, which is known to occur due to vascular factors. Metabolic factors such as serum electrolytes and blood lipids can play an important role in the pathogenesis and prognosis of stroke. Using a descriptive design, patient medical record data were collected and analyzed, which were then processed univariately, with a focus on serum electrolyte profiles, including sodium, potassium, and chloride, as well as blood lipid profiles, such as total cholesterol, LDL, and HDL. The results showed that the characteristics of stroke patients treated at Dr. Chasbullah Abdulmajid Hospital, Bekasi City, during the period from December 2024 to March 2025, differed only by gender, with 46 patients (50.5%) being male and 45 patients (49.5%) being female. The most common comorbid history in stroke patients was hypertension, totaling 53 people (58.3%), followed by diabetes mellitus, totaling 26 (28.6%). The largest electrolyte imbalance disorder was hypokalemia in 43 people (47.3%), followed by hyponatremia in 35 people (38.5%) and hyperchloremia in 23 people (25.3%). The majority of patients had low HDL levels, with 46 people (50.5%), 27 people (29.7%) having increased triglyceride levels, and 20 people (22.0%) having quite high cholesterol levels. These findings are expected to provide important insights for clinical management and prevention of stroke in the future.